From Genes to Health – Challenges and Opportunities - MANWAR HUSSAIN, MUHAMMAD RAMZAN; khan, Asifullah; Ali Mohamoud, Hussein Sheikh (Frontiers in Pediatrics, 2014)
In genome science, the advancement in high throughput sequencing technologies and bioinformatics analysis is facilitating the better understanding of Mendelian and complex trait inheritance. Charting the genetic basis of complex diseases- including pediatric cancer, and interpreting huge amount of next-generation sequencing data are among the major technical challenges to be overcome in order to understand the molecular basis of various diseases and genetic disorders. In this review we provide insights into some major challenges currently hindering a better understanding of Mendelian and complex trait inheritance, and thus impeding medical benefits to patients.